Volcanoes Segmentation at the Western Sunda Arc based on Satellite-derived Geological Lineaments and Land Surface Temperatures - Rahmanto, Ridwan; Saepuloh, Asep; Kriswati, Estu; Purnamasari, Heruningtyas Desi (Directorate for Research and Community Services, Institut Teknologi Bandung, 2025)
The Western Sunda Arc is an active tectonic zone formed by the subduction of the Indo-Australian Plate beneath the Eurasian Plate. The tectonic zone hosted for 83 active volcanoes, including Mts. Sinabung, Krakatau, Tangkuban Parahu, Merapi, and Semeru. The dense volcano concentration and high volcanic activity cause complexity in monitoring and observation processes. Segmenting volcanoes by location and tectonic setting is necessary to simplify the disaster monitoring and enhance mitigation efforts through focused observation areas. This study focuses on the segmentation of the volcanoes distributed at the Sunda Arc in Indonesia by analyzing the satellite-derived geological lineaments and land surface temperatures. The Sunda Arc is a complex volcanic chain that spans through Sumatra and Java Islands and lies in an active tectonic region. Remote sensing data and advanced geospatial techniques were used to examine geological lineament patterns and surface temperatures along the volcanic arc and the results were validated through fieldwork. Moreover, Shuttle Radar Topography Mission (SRTM) and Landsat 8 OLI/TIRS imagery were applied to achieve accurate lineament extraction and surface temperature anomaly detection. Lineament density was also computed through the modified Segment Tracing Algorithm (mSTA) to identify the fault zones and structural discontinuities in order to ensure better regional geological understanding. Subsequently, land surface temperature analysis was used to classify thermal anomalies and this led to the differentiation of natural volcanic sources from ground surfaces. These parameters were integrated to segment the volcanoes of the Sunda Arc into nine zones. Each zone was presented by average lineament density from 207.83 km/km2 to 166.06 km/km2, land surface temperature from 23.36 °C to 28.65 °C, angle of subduction slab from 22.871° to 38.007°, and lineament strikes from N 330° E to N 260° E. The zones were later discussed relative to the gradient of the Sunda Arc subduction slab as a form of contribution to the existing knowledge on geothermal dynamics, tectonic processes, and volcanic hazards beyond the region.